Analisis Dampak Program Pemberdayaan Bunda Mandiri Sejahtera (BISA) Dalam Meningkatkan Kesejahteraan Ekonomi Masyarakat - Bella Yulia Lestari; Faiza Nurul Ardila; Muhammad Shoufil Akbar; Roni Subhan (DPPM Universitas Pelita Bangsa, 2024)
LAZNAS Yatim Mandiri is a zakat amil institution that helps in empowering the economy of the families of orphans and poor people through the Bunda BISA program. The aim of this research was to describe the impact of the Bunda Mandiri Sejahtera empowerment program on improving the community's economy at LAZNAS Yatim Mandiri Jember. This research uses qualitative research methods to explore an in-depth understanding of the subject's experiences related to the phenomenon being researched. The results of the research show that the Mother Mandiri Sejahtera (BISA) program in Jember district can provide welfare to orphan mothers in the form of capital assistance and guidance so that orphan mothers can develop businesses that are managed to improve their economy. However, not all orphan mothers have a greater level of independence and curiosity in building their business. so that success in increasing their business is not the same as mothers who have not achieved their targets in their business.